Schistosomal appendicitis: Case series and systematic literature review. - Mateus Zacarias; Damiano Pizzol; Helder de Miranda; Anna Claudia Colangelo; Nicola Veronese; Lee Smith (Public Library of Science (PLoS), 2021)
Background Globally, schistosomiasis affects at least 240 million people each year with a high proportion of cases in sub-Saharan Africa. The infection presents a wide range of symptoms mainly at the gastrointestinal and urogenital level. Cases of schistosomiasis-related appendicitis are seldom reported. The aim of the present study is to identify the prevalence of schistosomiasis-related appendicitis in Beira, Mozambique and compare to global prevalence. Methods We retrospectively reviewed all cases of appendicitis recorded from January 2017 to March 2020 at a single pathology department located in Beira in order to assess the prevalence of schistosomiasis. Moreover, we performed a systematic review on the prevalence of schistosomiasis-related appendicitis in all countries. Findings A total of 145 appendicitis cases in Beira showed a 13.1% prevalence of schistosomal-related appendicitis. The mean age of patients was 29.1 years, and 14 (73.7%) were male. The systematic review identified 20 studies with 34,790 inpatients with schistosomiasis-related appendicitis with a global prevalence of 1.31% (95% confidence interval (CI): 0.72 to 2.06); a high heterogeneity (I2 = 96.0%) was observed. Studies carried out in Africa reported a significantly higher prevalence of schistosomiasis-related appendicitis (2.75%; 95% CI: 1.28 to 4.68) than those in Middle East (0.49%; 95% CI: 0.18 to 0.95) (p for interaction < 0.0001). Conclusions Schistosomiasis infection should be considered as possible cause of appendicitis not only in endemic areas but also in developed countries. Considering that prevention is the best way to control the infection, more efforts should be put in place in order to increase the prevention coverage and avoid the cascading implications for health. This is even more so important in this Coronavirus Disease 2019 (COVID-19) era where the majority of attention and funds are used to fight the pandemic.